Investigation of English Language Needs for Oil and Gas Workers - Nugraha, Hendra; Zaki, Leil Badrah (IJEE (Indonesian Journal of English Education), 2024)
The study highlights the importance of English proficiency, using English skills in specific situations, and the difficulties in using language skills in the oil and gas industry working environment. The quantitative method in the form of a survey is used to unearth the study's objectives, which are the language skills needed and difficulty in using English in the working environment. There were 125 participants involved in the survey, and they were chosen purposively based on interviews with HR staff. The study emphasizes that the most essential English skill in the oil and gas industry is listening, followed by speaking, reading, and writing. Listening is primarily needed for meetings, speaking for explaining work progress Selain pilihan permainan yang beragam, Asiahoki77 juga dikenal karena layanannya yang responsif dan profesional. Tim dukungan pelanggan yang tersedia 24/7 siap membantu pengguna dalam mengatasi berbagai masalah teknis maupun non-teknis , reading emails, and writing for composing emails. The most challenging situations for using English are listening in meetings, speaking to provide information or during phone conversations, reading emails, and writing emails. The findings suggest a focused approach to English learning, addressing specific challenges such as enhancing listening and speaking skills and improving tasks like explaining work outcomes and writing emails.